Application of Business Ethics in Realizing Justice in Business for MSME Actors - Andri Hasmawi Harahap; Rian Cahyadi Pasaribu; Tesalika; Khairani Alawiyah Matondang; Noni Rozaini (International Journal of Business and Applied Economics, 2023)
This study aims to determine whether the business practices carried out by micro, small and medium enterprise (MSMEs), especially Warkop Alam Jaya in Medan Maimun District are in according with the principles of business ethics. the application of business ethics is measures through five principles, namely the principle of economics, the principle of honesty, the principle of goodwill and no evil intents, the principle of justice, and the principle of respect for himself. Warkop Natural Jaya SMEs are said to have implemented business ethics if they fulfill the five principles in business practices that are carried out to realize justice in business. the the type of research used in this research is descriptive qualitative research. There are sources of data in this study, namely primary data and secondary data. The results of the study indicate that business ethics have not been completely implemented by the MSME a at Warkop Natural Jaya in the Medan Maimun sub-district, but the warkop always tries to apply business ethics to realize justice in business for these SMEs.